2016
DOI: 10.1016/j.archoralbio.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Lack of relationship between masticatory performance and nutritional status in adults with natural dentition

Abstract: ObjectiveThis study assessed the relation among several aspects of the masticatory function and the nutritional status in adults with natural dentition. DesignOne hundred adults with natural dentition participated in this cross-sectional study. They performed one free-style masticatory test consisting of five trials of 20 silicon-chewing cycles. The preferred chewing side was determined by calculating the asymmetry index. Masticatory performance was determined by sieving the silicon particles, and the cycle du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
(28 reference statements)
1
26
0
Order By: Relevance
“…Improving chewing efficiency only through a dental restoration does not necessarily change the dietary intake, as other factors such as habits, food preferences, general health, mobility, culture, and cooking skills -as well as cognitive impairment and appetitemay play a role 34,35 . While tailored nutritional counselling has been shown to increase the intake of fruits and vegetables in edentulous patients who were provided replacement dentures 36 , it should be borne in mind that oral health and chewing efficiency are only one piece of the puzzle that influences the nutritional state of elderly individuals 37 .…”
Section: The Benefits Of Retaining Natural Teeth Dietmentioning
confidence: 99%
“…Improving chewing efficiency only through a dental restoration does not necessarily change the dietary intake, as other factors such as habits, food preferences, general health, mobility, culture, and cooking skills -as well as cognitive impairment and appetitemay play a role 34,35 . While tailored nutritional counselling has been shown to increase the intake of fruits and vegetables in edentulous patients who were provided replacement dentures 36 , it should be borne in mind that oral health and chewing efficiency are only one piece of the puzzle that influences the nutritional state of elderly individuals 37 .…”
Section: The Benefits Of Retaining Natural Teeth Dietmentioning
confidence: 99%
“…one tooth replacement strategy over another in adult patients with reduced dentition (Elani, Starr, Silva, & Gallucci, 2018;McLister et al, 2018). A major objective of prosthodontic treatment is to restore or improve masticatory function (Jokstad, Orstavik, & Ramstad, 1998), which includes phenomena such as masticatory performance, masticatory laterality, and chewing rate (Flores-Orozco, Tiznado-Orozco, et al, 2016). Variations in masticatory performance may occur due to either extrinsic or intrinsic factors (Woda, Foster, Mishellany, & Peyron, 2006).…”
mentioning
confidence: 99%
“…Generally, the presence of fewer teeth results in poorer mastication. Several studies have shown that poor masticatory performance is a risk factor for being underweight . The number of occlusal contacts is also important for mastication .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that poor masticatory performance is a risk factor for being underweight. 5,26,27 The number of occlusal contacts is also important for mastication. [28][29][30] Fewer occlusal contacts between teeth in the premolar and molar regions are associated with lower mastication and chewing performance.…”
Section: P-valuementioning
confidence: 99%